FRACTURE PROPERTIES OF LOCAL ASPALT CONCRETE (Journal of Engineering, 2016)
The local asphalt concrete fracture properties represented by the fracture energy, J-integral, and stress intensity factor are calculated from the results of the three point bending beam test made for pre notches beams specimens with deformation rate of 1.27 mm/min. The results revealed that the stress intensity factor has increased by more than 40% when decreasing the testing temperature 10˚C and increasing the notch depth from 5 to 30mm. The change of asphalt type and content have a limited effect of less than 6%.